Affective Turn or Ecological Turn: Mary Oliver’s Poetry Revisited - Bazregarzadeh, Elmira (Anafora, 2024)
When it comes to discussions about affects, human beings become the center of attention. Yet, there are times when we find ourselves in some sort of in‐betweenness, where we cannot resolve whether we exert our influence on the non‐humans, or it is the non‐humans that trigger our bodies to respond in a certain way. The liminality witnessed at such times sheds light on the overlapping tendencies between ecocriticism and affect theory and encourages us to probe this issue more deeply. Accordingly, one may claim that a case study of Mary Oliver’s poems can fulfill the main objective of this short study regarding the fact that the mutuality of affect theory and ecocriticism can pave the way for gaining further insight into investigation of her poems, stemming from the fact that the speaker‐poet’s body and mind are the intersections of affective encounters with the rhythms of nature. The main conclusion that can be drawn from this research is that the application of the selected approach to Mary Oliver’s poetry will offer a workable solution to the mind/body dualism, whereby we witness the formation of various identities as a result of the effect of actions on other bodies and affective states.